Automated Video-Based Analysis Framework for Behavior Monitoring of Individual Animals in Zoos Using Deep Learning—A Study on Polar Bears - Zürl, Matthias; Stoll, Philip; Brehm, Ingrid; Raab, René; Zanca, Dario; Kabri, Samira; Happold, Johanna; Nille, Heiko; Prechtel, Katharina; Wünsch, Sophie; Krause, Marie; Seegerer, Stefan; et al. (Animals, 2022)
The monitoring of animals under human care is a crucial tool for biologists and zookeepers to keep track of the animals’ physical and psychological health. Additionally, it enables the analysis of observed behavioral changes and helps to unravel underlying reasons. Enhancing our understanding of animals ensures and improves ex situ animal welfare as well as in situ conservation. However, traditional observation methods are time- and labor-intensive, as they require experts to observe the animals on-site during long and repeated sessions and manually score their behavior. Therefore, the development of automated observation systems would greatly benefit researchers and practitioners in this domain. We propose an automated framework for basic behavior monitoring of individual animals under human care. Raw video data are processed to continuously determine the position of the individuals within the enclosure. The trajectories describing their travel patterns are presented, along with fundamental analysis, through a graphical user interface (GUI). We evaluate the performance of the framework on captive polar bears (Ursus maritimus). We show that the framework can localize and identify individual polar bears with an F1 score of 86.4%. The localization accuracy of the framework is 19.9±7.6 cm, outperforming current manual observation methods. Furthermore, we provide a bounding-box-labeled dataset of the two polar bears housed in Nuremberg Zoo.<br
Keywords: animal welfare; animal behavior; deep learning; object detection; animal monitoring; behavior observation; Ursus maritimus

Evaluation of Orthostatic Reactions in Real-World Environments Using Wearable Sensors - Happold, Johanna; Richer, Robert; Küderle, Arne; Gaßner, Heiko; Klucken, Jochen; Eskofier, Björn; Kluge, Felix (2021 43rd Annual International Conference of the IEEE Engineering in Medicine & Biology Society (EMBC), 2021)
As global life expectancy is constantly rising, the early detection of age-related, neurodegenerative diseases, such as Parkinson’s disease, is becoming increasingly important. Patients suffering from Parkinson’s disease often show autonomic nervous system dysfunction which is why its examination is an important diagnostic tool. Measuring the response of the heart rate (variability) to postural transitions and thereby assessing the orthostatic reaction is a common indicator of autonomic nervous system functioning. However, since these measurements are commonly performed in a clinical environment, results can be impaired by the white coat effect. To reduce this influence as well as inter- and intra-day variations, our work aims to investigate the assessment of orthostatic reactions in free-living environments. We collected IMU and ECG data of seven healthy participants over four days and evaluated differences in orthostatic reactions between standardized tests at lab, at home, as well as unsupervised recordings during real-world conditions. Except for the first lab recording, we detected significant changes in heart rate due to postural transitions in all recording settings, with the strongest response occurring during standardized tests at home. Our findings show that real-world assessment of orthostatic reactions is possible and provides comparable results to supervised assessments in lab settings. Additionally, our results indicate high inter- and intra-day variability which motivates the continuous orthostatic reaction measurement over the span of multiple days. We are convinced that our presented approach provides a first step towards unobtrusive assessment of orthostatic reactions in real-world environments, which might enable a more reliable early detection of disorders of the autonomic nervous system.
Keywords: Atmospheric measurements; Autonomic nervous system; Tools; Electrocardiography; Particle measurements; Biology; Reliability